A democratic program for healing: The Raspail domestic medicine method in 1840s France. Issue 4 (December 2020) - Guillemain, Hervé
Argument: Raspail's domestic medicine method, popularized in 1840s France, has similarities with the practices of nineteenth century non-academic healers. His mass marketing of camphor as a universal treatment echoes the practices of "charlatans" and their circles. But Raspail is also very original in this history of popular care. As a scientist, a popularizer of encyclopedic knowledge and a political activist, he managed to blur traditional distinctions between science and politics and between popular and learned medicine. Raspail was a constant thorn in the side of academic institutions and professional organizations, which were struggling to gain legitimacy. His work took a political turn when he combined, within a single project, his approach to treatment and his call for democratizing medical care. Raspail's method challenged institutional norms by acknowledging the importance of the patient's contribution to the healing process, and recognizing the necessity of thwarting the occasionally deleterious effects of monopolistic medicalization.